PENGARUH KEPUTUSAN PEMBELIAN MELALUI E-COMMERCE SHOPEE TERHADAP PERILAKU KONSUMTIF MAHASISWA (Studi Kasus Fakultas PIPSB Institut Pendidikan Tapanuli Selatan) - Rosnida Siregar; Mariyatul Kubtiyah Ritonga; Sri Hartini; Nadira Damayanti; Tondi Riadi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This study aims to determine 1) Description of Purchasing Decisions Through Shopee E-Commerce, 2) Description of Consumptive Behavior 3) Seeing the Significant Influence Between Purchasing Decisions Through Shopee E-Commerce on Consumptive Behavior of Students of the Faculty of PIPSB, South Tapanuli Education Institute. This study uses a descriptive quantitative method with a population of all students of the Faculty of PIPSB, South Tapanuli Education Institute and a sample of 40 students. Data processing is carried out using simple linear regression test analysis techniques, t-tests, and coefficient of determination tests supported by using IBM SPSS version 29 statistical tests. Based on data analysis, it is known that the description of purchasing decisions through Shopee e-commerce obtained an average value (mean) of 61 in the high category. The description of consumptive behavior of students of the Faculty of PIPSB, South Tapanuli Education Institute obtained an average value (mean) of 59 in the sufficient category. Based on data processing using SPSS version 29, the calculated t-value (7.990) > t-table (1.686) was obtained, with a significance value of 0.000 at a 95% confidence level or a 5% margin of error. Therefore, the significance value is less than 0.05 (0.000 < 0.05). This means there is a significant influence between Purchase Decisions Through Shopee E-Commerce on the Consumptive Behavior of Students of the Faculty of PIPSB, South Tapanuli Education Institute.